PENGARUH LINGKUNGAN SOSIAL DAN GAYA HIDUP TERHADAP PERILAKU KONSUMSI MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNS - Hartiyani Sadu Budanti; Mintasih Indriayu; Muhammad Sabandi (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2017)
This study aims to determine: (1) the influence of social environment towards students’ consumption behavior. (2) The influence of lifestyle towards students’ consumption behavior. (3) the influence of social environment and lifestyle towards students’ consumption behavior of Economic Education Study Program Teacher Training and Education Faculty Sebelas Maret University of Surakarta.The research method used is descriptive method with quantitative approach.The sample used is 128 students of Economic Education Study program. Data analysis techniques used is multiple liniear regression analysis.  Based on the results of the study, it can be concluded that: There is significant influence between social environment and lifestyle towards students’ consumption behavior of Economic Education Study Program Teacher Training and Education Faculty Sebelas Maret University of Surakarta. The value of coefficient of determination (adjusted R2) of 0.095, meaning 9,5% of student consumption behavior is influenced by social environment and lifestyle, while 90,5% is influenced by other factor.